Resepsi Az-Zamakhsyarī atas Wacana Teologis Muktazilah: Bias al-Uṣūl al-Khamsah dalam Tafsir al-Kasysyāf - Mahmud, Muhammad Aziz (Contemporary Quran, 2023)
The debate regarding the presence of Mu’tazilah concepts in the interpretation of al-Kasysyāf remains a topic of discussion in interpretive literature. This debate stems from az-Zamakhsyarī’s theological identity as a proponent of Mu’tazilah thought. This study seeks to re-examine how az-Zamakhsyarī integrated Mu’tazilah conceptions into his work, al-Kasysyāf, by focusing on the dominant linguistic elements of his interpretation. To achieve this, the research adopts a qualitative approach, utilizing content analysis as the primary tool for data analysis. Additionally, the study employs a representation model to differentiate the ways in which az-Zamakhsyarī received and applied Mu’tazilah teachings. The findings reveal that az-Zamakhsyarī’s extensive use of linguistic analysis in interpreting the Quran often led to clear statements affirming his Mu’tazilah stance. However, he appears ambiguous when addressing the concept of the Oneness of God, a core tenet of Mu’tazilah doctrine, which was a sensitive issue in his time. This ambiguity is also evident in discussions concerning the ontological nature of God, where az-Zamakhsyarī tends to avoid the in-depth linguistic exploration seen in other areas, differing from his approach in al-Minhāj fi Uṣūl ad-Dīn. This reluctance to delve into sensitive topics leads to a diminished presence of Mu’tazilah narratives in al-Kasysyāf, contributing to varied interpretations of its content regarding Mu’tazilah teachings in Quranic exegesis.